HUBUNGAN ANTARA FAKTOR KESELAMATAN BERKENDARA DENGAN PERILAKU KESELAMATAN BERKENDARA - Nova Mega Muryatma (Universitas Airlangga, 2018)
Surabaya is the capital city of East Java Province and is a large city with a population of 2,807 inhabitants. According to WHO in 2011 showed that 400,000 victims under the age of 25 who died on the highway, with an average mortality rate of 1,000 children and adolescents each day. The cause of the greatest accidents is caused by human factors that do not apply discipline in traffic, low awareness, and lack of knowledge about safety riding. The purpose of this study is to analyze the relationship between safety factor driving with saefty riding behavior on students of SMK PGRI 4 Surabaya. This research is an observational analytic research using research method with cross sectional design. The sample of 74 respondents was taken randomly using simple random sampling technique. Data collection using questionnaires tool filled by respondents. Data analysis in this study using Chi Square test with 5% significance value to see the relationship between independent variables with dependent variable. Based on the research conducted there is no significant relationship between independent variables with dependent variable with p-value exceed the value of meaning. In order to minimize the incidence of traffic accidents involving students it is good that schools always do the provision of a bound regulation that students are required to use SNI helmets when riding a motorcycle, no need to use expensive helmet but just use a helmet that complies with safety standards. Facilities for students are expected to always comply with existing traffic rules while driving. Keyword: safety riding, student, safety riding behaviour